2013
DOI: 10.1089/jpm.2013.0050
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Effect of Existential Behavioral Therapy for Bereaved Partners: A Qualitative Study

Abstract: The categories considered as being helpful parallel core elements of EBT and recent grief theories. The intervention was found to be supportive and met the needs of the participants. The interviewees appreciated the continuity of EBT support from palliative care into bereavement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(30 citation statements)
references
References 24 publications
1
28
0
1
Order By: Relevance
“…44,47 These understandings in turn helped them to accept these experiences 61 and 'not fear' their feelings. 47 Groups in five studies were found to be helpful for enabling self-disclosure and the expression of grief, emotions and the 'venting' of experience, 51,60,61,64,74 as well as pleasant memories. 58 In the music therapy group, participants described how the spiritual connection to the deceased that they experienced helped to resolve their grief.…”
Section: Evidence On the Impact Of Interventionsmentioning
confidence: 95%
See 3 more Smart Citations
“…44,47 These understandings in turn helped them to accept these experiences 61 and 'not fear' their feelings. 47 Groups in five studies were found to be helpful for enabling self-disclosure and the expression of grief, emotions and the 'venting' of experience, 51,60,61,64,74 as well as pleasant memories. 58 In the music therapy group, participants described how the spiritual connection to the deceased that they experienced helped to resolve their grief.…”
Section: Evidence On the Impact Of Interventionsmentioning
confidence: 95%
“…And we shared this with each other. (Participant) 61 Sense of mastery and moving ahead. Twelve studies described benefits relating to coping, mastery and moving ahead.…”
Section: Evidence On the Impact Of Interventionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Es fehlt mir!" Die individuell erlebten Wirkfaktoren der Intervention wurden zudem ausführlich in qualitativen Interviews untersucht [4]. Hierbei erwiesen sich insbesondere der Support durch die Gruppenatmosphäre und die Strategien zur Emotionsregulation/Achtsamkeitsübungen als wirksam.…”
Section: Subjektive Einschätzung Der Gruppenelementeunclassified